Avaliação da qualidade dos serviços de suporte em Tecnologia da Informação em uma Instituição Federal de Ensino Superior - Farrapo Júnior, Antonio Carlos (2019)
The assessment of the information technology service quality provided by private or public organizations to its internal clients is an essential requirement to achieve a competitive advantage. The present study aimed to evaluate the quality of information technology support services in a federal higher education institution (IFES) and to analyze how quality in services, with its dimensions, is related to satisfaction, in the context of IT service management in an IFES. Therefore, a systematic literature review on quality assessment models in IT services was performed, which provided the theoretical basis for operationalizing the SERVQUAL instrument. After the theory articulation, a survey was conducted where the sample was obtained with a respondent rate of 37% of the population of 271 users. Data analysis was performed using descriptive statistics and structural equation modeling technique, which supported the refinement of the instrument. The results exposed gaps in the five dimensions of quality during evaluated services. The dimensions of empathy and reliability reached the highest values. It was further observed that the quality of services, with their respective dimensions, positively influences user satisfaction. IT-based SERVQUAL proved to be adequate for assessing the IT support service quality provided by an IFES. Aforementioned allows the instrument to be applied as a reference by other IFES to improve IT service management. Additionally, the research reinforces the existence of a positive relationship between service quality and satisfaction, allowing managers to properly allocate available resources.